2013
DOI: 10.5586/am.2012.006
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and cytotoxic activity of the polysaccharide fractions in Sarcodon imbricatus (Basidiomycota)

Abstract: The aim of the study was chemical analysis of polysaccharide fractions from sporocarps of <em>Sarcodon imbricatus</em> collected in natural sites and from the mycelium of <em>in vitro</em> cultures. Three polysaccharide fractions (F<sub>O</sub>I, F<sub>O</sub>II, F<sub>O</sub>III) were isolated from sporocarps and two (F<sub>K</sub>I, F<sub>K</sub>II) from <em>in vitro</em> cultures. Qualitative analysis by HPLC met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Sarcodon imbricatus (SI), belonging to the family of Basidiomycotina and Aphyllophorales , is an edible and medicinal fungus, widely distributed in Central Europe and in North America [ 18 ] and also produced in Tibet, Gansu, Anhui, northwestern Yunnan, and western Sichuan of China [ 19 ]. Although SI is described to show various pharmacological activities including anti-inflammation and anticancer in the folk, previous studies mainly focused on its chemical component analysis and polysaccharide isolation [ 20 , 21 ]. Our group has already confirmed the immunomodulatory property of S. imbricatus water extracts in the cyclophosphamide- (CTX-) induced immunosupressive mouse model, which is related to its modulation on oxidative stress [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sarcodon imbricatus (SI), belonging to the family of Basidiomycotina and Aphyllophorales , is an edible and medicinal fungus, widely distributed in Central Europe and in North America [ 18 ] and also produced in Tibet, Gansu, Anhui, northwestern Yunnan, and western Sichuan of China [ 19 ]. Although SI is described to show various pharmacological activities including anti-inflammation and anticancer in the folk, previous studies mainly focused on its chemical component analysis and polysaccharide isolation [ 20 , 21 ]. Our group has already confirmed the immunomodulatory property of S. imbricatus water extracts in the cyclophosphamide- (CTX-) induced immunosupressive mouse model, which is related to its modulation on oxidative stress [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were then injected into the HPLC system, equipped with a refraction-index (RI) detector. LC-NH 2 column (Sigma) was used for the chromatographic separation of reducing sugars [80]. Glucose, galactose, fucose, mannose, xylose, and arabinose (Sigma) were used as standards.…”
Section: Monosaccharide Compositionmentioning
confidence: 99%
“…Recent studies have demonstrated that Sarcodon imbricatus is also important as an agent that stimulates neuronal growth and promotes brain health [8]. Our previous studies of S. imbricatus indicated antimicrobial activity against five strains of Gram-positive and Gram-negative bacteria, antiviral activity against HPV-1 virus, and cytotoxic activity toward B16 murine melanoma tumor cell lines, sarcoma XC, and human breast cancer cell line in vitro of selected polysaccharide fractions isolated from mycelial cultures of this fungal species [9,10].…”
Section: Introductionmentioning
confidence: 99%